KARAKTERISTIK GEOKIMIA LEMPUNG DAN KUALITASNYA SEBAGAI PENJERNIH MINYAK SAWIT DI KABUPATEN SUKABUMI, JAWA BARAT - Insan, Rachmatulloh; Hutabarat, Johanes; Haryanto, Agus Didit (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
Before palm oil can be consumed, it must be processed through several processes, one of them is purification. To obtain an oil colour corresponds to a certain quality, a bleaching process is required using a bleaching agent or bleaching earth (BE). Material of palm oil purifier is made from clay. Clay is often found in Sukabumi Regency, West Java Province in Jampang Formation Cikarang Member and Lengkong Formation. The purpose of this research is to obtain a geochemical description and to determine the chemical composition of clay minerals in Jampang Formation Cikarang Member and Lengkong Formation and its effect on surface area properties and bleaching performance. This research used five clay samples, three samples from Jampang Formation Cikarang Member and two sampels from Lengkong Formation. To obtain geochemical characteristics composition, each sample was analyzed using XRD, SEM and XRF methods, meanwhile, to obtain information on the quality of palm oil clarifier, surface spesific area of the clay was measured using SAA and the color index of the palm oil that had been filtered by each clay sample was measured using the Lovibond Tintometer. The results showed that there was correlation between montmorillonite content to surface area value and bleaching performance of the clay. The larger the surface area of the clay, the higher its bleaching ability for palm oil. In addition, the surface area of the clay is also related to its montmorillonite content. Clay samples with high surface area, namely sample FJ-1 with a surface area of 111.5 m²/g and FJ-2 with a surface area of 106.4 m²/g, have higher montmorillonite content, specifically 67.2 and 70.7% compared to samples FJ-3, FL-1, and FL-2, which have montmorillonite contents of 17.4%, 47.4%, and 32.9%. Therefore, to obtain high-quality clay as a bleaching earth (BE) for the palm oil industry, clay with a high montmorillonite mineral content should be used.